German and Italian Pensions: Similar Roots, Different Reform Paths, Comparable Trajectories?. Issue 3 (3rd July 2021) - Guardiancich, Igor; Natali, David
Abstract : The article employs a multi-level analytical framework to analyse pension reforms in Germany and Italy between 2011 and 2018, thereby focusing on the role played by the European Union. Whereas the EU is able to react to crises and prevent major deviations from its priorities, its influence has been uneven in the face of policy reversals and its capacity to spur the convergence of the two political economies has been limited. On one hand, the Commission's recommendations to rebalance pension spending have not been fully followed in either country. On the other, pension-related interventions can only do so much to reduce labour market frictions (a problem particularly felt in Italy). Theoretically, the article innovates the literature on pensions in three respects. First, the study employs a three-level game, where not only the EU and policymakers interact, but also financial markets have an influence. Second, the article provides evidence of the persistent political nature of EU pension policymaking. Consequently, both EU and domestic policymakers have margins to interpret the rules. Third, the piece shows that the EU has little direct influence on reform outcomes. Contingent factors, such as the economic cycle, play a role in shaping the economic indicators of pensions.